2020
DOI: 10.1111/1462-2920.15119
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the current knowledge and biotechnological applications of the oxygen‐independent ortho‐phthalate degradation pathway

Abstract: Summary ortho‐Phthalate derives from industrially produced phthalate esters, which are massively used as plasticizers and constitute major emerging environmental pollutants. The pht pathway for the anaerobic bacterial biodegradation of o‐phthalate involves its activation to phthaloyl‐CoA followed by decarboxylation to benzoyl‐CoA. Here, we have explored further the pht peripheral pathway in denitrifying bacteria and shown that it requires also an active transport system for o‐phthalate uptake that belongs to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…chlorobenzoate DSM 18012 (on chromosome) ( 19 ). Furthermore, Sanz et al ( 43 ) suggested that the complete o -phthalic acid degradation pathway in denitrifying bacteria, together with the o -phthalic acid transporter gene, is successfully transferred to heterologous bacteria that are unable to use o -phthalic acid as a substrate. In the present study, a similar observation was made in DEHP side chain-degrading Burkholderiales Bin13 and o -phthalic acid-degrading Aestuariibacter Bin44.…”
Section: Discussionmentioning
confidence: 99%
“…chlorobenzoate DSM 18012 (on chromosome) ( 19 ). Furthermore, Sanz et al ( 43 ) suggested that the complete o -phthalic acid degradation pathway in denitrifying bacteria, together with the o -phthalic acid transporter gene, is successfully transferred to heterologous bacteria that are unable to use o -phthalic acid as a substrate. In the present study, a similar observation was made in DEHP side chain-degrading Burkholderiales Bin13 and o -phthalic acid-degrading Aestuariibacter Bin44.…”
Section: Discussionmentioning
confidence: 99%
“…PA01 (on chromosome), and T. chlorobenzoate DSM18012 (on chromosome) [19]. Furthermore, Sanz [42] suggested that the complete o-phthalic acid degradation pathway in denitrifying bacteria, together with the o-phthalic acid transporter gene, is successfully transferred to heterologous bacteria that are unable to use ophthalic acid as a substrate. In the present study, a similar observation was made in DEHP sidechains-degrading Burkholderiales Bin13 and o-phthalic acid-degrading Aestuariibacter Bin44.…”
Section: Discussionmentioning
confidence: 99%
“…A TAXI transporter from Azoarcus sp. CIB has been shown to transport orthophthalate 38 , and phenotypic analysis of a TAXI gene knockout in Psychrobacter arcticus suggest it is involved in the uptake of butyrate, glutamate, fumarate, and acetate 39 . This limited number of examples hints that TAXIs can also transport a range of substrates akin to the DctP-type TRAPs.…”
Section: Introductionmentioning
confidence: 99%